Recognised grounds for dismissals unter industrial relations law a study of Malaysian decisions / Aziz Mohd. Than - Mohd. Than, Aziz (Faculty of Law, 1987)
With the transition of our country as a mainly agricultural country into a partially industrialised one,peace and harmony between employer and worker has become of great concern not only to the parties but also to the country as a whole, if the successive five year plans are to be successfully implemented to increase the siza of the national cake and improve the lot of all Malaysians.